x=-3 y=0 probably wrong but it’s the root of at least one of these
Answer: C. (-4, -2)
<u>Step-by-step explanation:</u>
First, eliminate one of the variables and solve for the remaining variable:
2x - 5y = 2 → 3(2x - 5y = 2) → 6x - 15y = 6
3x + 2y = -16 → -2(3x + 2y = -16) → <u> -6x - 4y = 32</u>
-19y = 38
y = -2
Next, replace "y" with -2 into either of the original equations to solve for x:
2x - 5y = 2
2x - 5(-2) = 2
2x + 10 = 2
2x = -8
x = -4
x = -4, y = -2
<u>Check:</u>
Plug in the x- and y-values into the other original equation:
3x + 2y = -16
3(-4) + 2(-2) = -16
-12 + -4 = -16
-16 = -16 
Answer:
12 cups
Step-by-step explanation:
If the size of the bag decreased by 20%, so will the number of cups held.
Number of cups held before the change = 15 cups
If the number of cups held after the 20% reduction in the size of the bag
= (100 - 20)% × 15
=80% × 15
= 12 cups
The new bags will hold 12 cups.